A pediatric patient case of vesicoureteral reflux: Successful healing using Yoga Prana Vidya protocols - Gupta, Yashika; Satyanarayana Nanduri, Venkata (Indian Journal of Child Health, 2024)
Vesicoureteral reflux (VUR) is characterized by abnormal urine flow from the bladder back through the ureters, finally reaching the kidneys. The disease is usually symptomless and is diagnosed accidentally when patients suffer from febrile urinary tract infections. Many treatment guidelines are available ranging from medicine to surgery. However, management is a clinical art. Here, we present a pediatric case of VUR healed by Yoga Prana Vidya (YPV) therapies without surgery. The normal condition of the patient’s kidneys and bladder was achieved within 2½ months of the YPV healing intervention. This case shows that YPV protocols have successfully treated a pediatric VUR condition without the need for surgery. Further research using appropriate sample and methodology is recommended.